Locus of Control and Investment in Risky Assets - Nicolas Salamanca; Andries de Grip; Didier Fouarge; Raymond Montizaan (Institute of Labor Economics (IZA), 2016)
We show that household heads with a strong internal economic locus of control are more likely to hold equity and hold a larger share of equity in their investment portfolio. This relation holds when we control for economic preferences and possible confounders such as financial literacy, overconfidence, optimism, trust, and other personality traits. We argue that this relation is driven by a link between internal economic locus of control and a lower perception of the risk of investing inequity. Those with a strong internal economic locus of control perceive less variance in equity, making these investments more attractive.
Keywords: G11; D14; D19; 330; household portfolios; personality traits; risk and time preferences; risk perception